Pengembangan Media Belajar Klasifikasi Hewan Laut Berbasis Android Markerless AR - Nadila, Syalsa; Imanullah, Muhammad; Darnita, Yulia; Darmi, Yulia (Institut Bakti Nusantara, 2024)
From the research that has been carried out regarding Android-based Augmented Reality Technology for Learning Media for the Classification of Marine Animals, the conclusion is, the creation of an Augmented Reality application that studies the classification of marine animals which can operate on an Android smartphone. Using 3D objects it can be visualized so that it can be like real on mobile devices when the camera detects markers with rough architecture such as floors, tables and others, with distances when tracking scan markers, namely 10cm, 20cm and 30cm. The better the lighting in a room, the faster the marker will be recognized, and conversely, when the marker is in a state where there is a lack of room light, the system cannot detect the marker.